The Evaluation of Implementation of the 2013 Curriculum of Physical Education Sports and Health at Public Junior High Schools in Klaten Regency - Rachmat, Basuki; Soegiyanto, Soegiyanto; Rumini, Rumini (Journal of Physical Education and Sports, 2019)
This study is aimed at determining the implementation of the 2013 curriculum in PJOK subjects in aspects: learning management and student services, learning process, assessment process, constraints encountered. This research is used a mixed-method approach which is a qualitative approach supported by a quantitative approach with a formative evaluation design developed by Scriven. The Subject in this study was SMPN 1 Delanggu, SMPN 2 Klaten, SMPN 1 Prambanan, SMPN 1 Jatinom, dan SMPN 1 Karangdowo. To collect data is used data collection techniques interviews, observation, and documentation. Data analysis techniques were used descriptive qualitative analysis supported by a quantitative approach that is data collection, data reduction, data presentation, and drawing conclusions. The results showed that aspects are implemented well, with an average score of 3.64 and 3.18, are implemented well, with an average score of 3.64 and 3.28, was carried out well with an average score of 4, the results of outcome are less than optimal and making the assessment rubric still lack and the teacher feels that media facilities still limited. Conclusions: learning management and student services are implemented well, the learning process is done well, the assessment process was carried out well, constraints on the implementation of the 2013 curriculum inputting value (IT), the results is using the command method, assessing the attitude is less than optimal and making the assessment rubric still lack and the teacher feels that media facilities still limited.